Design Considerations for Sub-1-V 1T1C FeRAM Memory Circuits - Mohammad Adnaan; Sou-Chi Chang; Hai Li; Yu-Ching Liao; Ian A. Young; Azad Naeemi (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
We present a comprehensive benchmarking framework for one transistor-one capacitor (1T1C) low-voltage ferroelectric random access memory (FeRAM) circuits. We focus on the most promising ferroelectric materials, hafnium zirconium oxide (HZO) and barium titanate (BTO), known for their fast switching speeds and low coercive voltages. We model ferroelectric capacitors using physics-based phase-field models and calibrate the polarization switching speed and hysteresis loop versus experimental data. Ferroelectric memory cells are designed using a 28-nm process design kit (PDK), incorporating peripheral circuitry and interconnect parasitics. We set up the memory array circuit design and analyze its performance by varying the row/column size of the memory array, as well as driver and capacitor sizes. Our results are compared with other emerging memory technologies, particularly magnetic/spintronic memories, in terms of read/write latencies and energy consumption. We identify the critical aspects of the ferroelectric memory array performance, such as the effect of plateline driver and bitline capacitances, and provide recommendations to further optimize the performance of such low operating voltage ferroelectric memory circuits.